Appraising the effectiveness of pipeline interlinks in the distribution of refined petroleum products in Nigeria. - Dike, Onwubiko N.; Onwuka, Emmanuel (Advances in Social Sciences Research Journal, 2015)
This study attempted to appraise the effectiveness of pipeline interlinks in the distribution of refined petroleum products to the depots in Nigeria. The population of the study was 1468 comprising, Category A: Oil Marketers, 1258 (Major and Independent Marketers), Category B: Policy makers, 110 (Nigerian National Petroleum Corporation (NNPC) and Petroleum Products Pricing Regulatory Agency (PPPRA.), Category C: Pipeline and Products Marketing Company, 100 (PPMC). A sample size of 314 was drawn using Yamane (1964) formula. The sample size for each category was determined by the application of Bowley’s proportional allocation formula. Primary and secondary data were accessed. In-depth interviews were held. The questionnaire was structured based on the five point Likert scale format. Opinions of marketing experts were used in the questionnaire validation. The scores derived from the pilot study were subjected to Cronbach Alpha technique and the reliability coefficient of the research instrument, 0.985 was determined. Using one way ANOVA statistical technique and Minitab software package, the hypothesis was tested at 0.05 level of significance and 9 degrees of freedom. The study revealed that the effectiveness of pipeline interlinks at 13.70 percent was non-significant for effective distribution of refined petroleum products to the depots across the country. Recommendations were made.